(3GdeajO aj TQM YeOI GdeLjO aj GdfXe hGdJLhjOs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HMaX cJGHg hHYO aEf CaVd eG TZd GdYHO Hg dSGfg hYeQ Hg bdHg hMfGfg cJGH Gddg GdeLjO hdeG cGfJ fhfjI GdEeGe GdedbH HYde GdOjf GdeSeGg YeOg GdeLjO Cf CTQMgG TQMkG jYjf Ydi agegG s
(3BNQgG (B:s
(3hGdZQV ef gPg GdCHjGJ GdJfHjg Ydi eG JMdJ Hg gPg GdbUjOI ef fXe HOjY GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
Keywords: (3GdbQGAGJ hGdJLhjOs